Overview of Macro Nutritional Substance (Carbohydrate, Protein, Fat) in Children Aged 12-59 Months Getting Recovery PMT in Puskesmas Nusa Indah Bengkulu City - Ega Purwita Sari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Toddlers are children who have reached the age of one year or are commonly used to calculate the age of 12-59 months (Muaris, 2006). Experts classify the age of the toddler as a stage of development of children who are quite susceptible to various diseases, including diseases caused by lack or excess intake of certain types of nutrients. Every year more than a third of child deaths in the world are related to malnutrition. The study design uses quantitative descriptive with cross sectional approach. with a total sampling technique in accordance with inclusion criteria. Toddlers who get Recovery PMT at Nusa Indah Health Center., Willing to be sampled by using a statement willing to be a respondent (informed Consent), and Residing in the Nusa Indah Health Center Working Area Bengkulu City. Based on the results of statistical tests with univariate test analysis it was found that 17 (89.5%) had less carbohydrate intake, (42.1%) had less protein intake, and 78.9%) had less fat intake. The results of research on the description of macro nutrient intake (carbohydrates, protein, fat) in infants aged 12-59 months received PMT Recovery at the Nusa Indah health center can be concluded that the majority of toddlers aged 12-59 months received PMT Recovery in Nusa Indah has less carbohydrate intake, Most of toddlers aged 12-59 months get Recovery PMT in Nusa Indah have less protein intake, Most toddlers aged 12-59 months get Recovery PMT in Nusa Indah have less fat intake.